Immune Co-inhibitory Receptors CTLA-4, PD-1, TIGIT, LAG-3, and TIM-3 in Upper Tract Urothelial Carcinomas: A Large Cohort Study. Issue 4 (5th May 2023) - Jin, Shengming; Shang, Zhi; Wang, Wenwen; Gu, Chengyuan; Wei, Yu; Zhu, Yu; Yang, Chen; Zhang, Tiantian; Zhu, Yao; Zhu, Yiping; Wu, Junlong; Ye, Dingwei
Abstract : Programmed cell death 1 ligand 1), programmed cell death protein-1 (PD-1), cytotoxic T-lymphocyte antigen 4 (CTLA-4), T-cell immunoglobulin and mucin-domain containing-3, lymphocyte activation gene-3, and T-cell immunoglobulin and ITIM domain (TIGIT) are considered major immune co-inhibitory receptors (CIRs) and the most promising immunotherapeutic targets in cancer treatment, but they are largely unexplored in upper tract urothelial carcinoma (UTUC). The aim of this Cohort Study was to provide evidence concerning expression profiles and the clinical significance of CIRs among Chinese UTUC patients. A total of 175 UTUC patients who received radical surgery in our center were included. We used immunohistochemistry to evaluate CIR expressions in tissue microarrays (TMAs). Clinicopathological characteristics and prognostic correlations of CIR proteins were retrospectively analyzed. TIGIT, T-cell immunoglobulin and mucin-domain containing-3, PD-1, CTLA-4, Programmed cell death 1 ligand 1, and lymphocyte activation gene-3 high expression was examined in 136(77.7%), 86(49.1%), 57(32.6%), 18(10.3%), 28(16.0%), and 18(10.3%) patients, respectively. Log-rank tests and Multivariate Cox analysis both implied CTLA-4 and TIGIT expression was associated with worse relapse-free survival. In conclusion, this is the largest Chinese UTUC cohort study, and we analyzed the Co-inhibitory receptor expression profiles in UTUC. We identified CTLA-4 and TIGIT expression as promising biomarkers for tumor recurrence. Furthermore, a subset of advanced UTUCs are probably immunogenic, for which single or combined immunotherapy may be potential therapeutic approaches in the future.